Genetic Approaches to the Molecular/Neuronal Mechanisms Underlying Learning and Memory in the Mouse - Akira Nakajima; Ya-Ping Tang (Elsevier, 2005)
Learning and memory is an essential component of human intelligence. To understand its underlying molecular and neuronal mechanisms is currently an extensive focus in the field of cognitive neuroscience. We have employed advanced mouse genetic approaches to analyze the molecular and neuronal bases for learning and memory, and our results showed that brain region-specific genetic manipulations (including transgenic and knockout), inducible/reversible knockout, genetic/chemical kinase inactivation, and neuronal-based genetic approach are very powerful tools for studying the involvements of various molecules or neuronal substrates in the processes of learning and memory. Studies using these techniques may eventually lead to the understanding of how new information is acquired and how learned information is memorized in the brain. Keywords:: behavior, knockout, learning and memory, mouse, transgenic